Spatial and temporal variation of pneumonia incidence among under-five children in central gondar zone, Northwest Ethiopia, 2013- 2022 - Kidist Asrat Degif; Mulat Gebrehiwot; Garedew Tadege; Lidetu Demoze; Gelila Yitageasu (BMC Pediatrics)
Abstract Pneumonia is one of the major causes of morbidity and mortality among under-five years old children’s worldwide, with Ethiopia having the highest rates among Sub-Saharan African nations. Effective control and preventative measures will be made clear by comprehending the spatial, temporal, and spatiotemporal variation of pneumonia incidence among under-five children. A time series cross-sectional study design was conducted from 1 January 2013 to 31 December 2022 using pneumonia reports obtained from the Central Gondar Zone health department and Gondar administrative health department. Fifteen districts and one administrative city were included and geocoded in the study. Spatial, temporal, and space-time scan spatial statistics were employed to identify clusters of pneumonia incidence among under-five children and were performed by using Excel and the SaTScan program, and the map was plotted using ArcGIS. Pneumonia incidence among under-five children reveals a general trend of rise and seasonal variation in the study area. During this study period, 147,294 under-five cases of pneumonia were reported and males made up most cases accounting for 54.94%. The average cumulative incidence proportion was 9.1. Purely high-rate spatial clusters were detected in Dembiya, Chilga, Wogera, and Gondar Zuria between 2013 and 2018. Gondar City, Wogera, and Gondar Zuria were high-rate spatial clusters detected between 2019 and 2022. The purely temporal cluster was observed from 2017 to 2018 and 2021 to 2022. Spatiotemporal clusters were detected in Dembia, Chilga, Gondar Zuria, and Wogera from 2013 - 2018 and in Gondar City, Wogera, and Gondar Zuria from 2019 - 2022. During this period pneumonia showed seasonal variation with two major peak months namely in April and October. Under five children pneumonia was found to have spatial, temporal, spatiotemporal clustering, and seasonal patterns. Also, the incidence increased over time. Interventional and preventive strategies should be developed and given priority to the areas that have been detected as hot spots in this study to reduce the mortality and morbidity of under 5 children caused by pneumonia.